A Case of Acute Lymphocytic Leukaemia with t(3;13) and Central Nervous System Leukemia after Allogenic Cord Blood Transplantation. (4th September 2019) - Li, Xiaofan; Hong, Yaqun; Huang, Jiafu; Li, Nainong
Background: Acute lymphoblastic leukemia (ALL) is a neoplastic cancer characterized by clonal expansion of leukemic cells in lymph organs and bone marrow. Lots of kinds of different chromosomal translocations can be found in those leukemic cells. However, the role of abnormal chromosomes and genes in leukemogenesis is not yet fully understood. Identifying new chromosomal translocations can facilitate a better understanding of pathogenesis of this disease. Case presentation: We report a rare case of acute lymphocytic leukaemia with t(3;13)(q29, q21). The patient was diagnosed pre-B-ALL with no abnormal chromosomal or gene fusion and achieved complete remission (CR) after induction chemotherapy; 10 months later, she relapsed in the consolidation, with cytogenetics tests showing 46, XX, t(3;13)(q29, q21). Given no CR after two chemotherapy regimens, the patient received salvage cord blood transplantation. Regular intrathecal methotrexate was applied to prevent central nervous system leukemia. Good graft versus leukemia was induced by daily injection of a low dose of IL-2 2 months post-transplantation. Minimal residual disease negativity was maintained until central nervous system (CNS) leukemia was found 8 months after transplantation. A whole exome sequencing was performed. Nine driver mutation genes and seven tumor genes were found. Conclusions: We highly suspect that the relapse in the CNS after transplantation is associated with a rare chromosomal translocation.